Water insecurity in Sri Lanka, 2024-2025: Evidence from the 2024-2025 BRIGHT survey - Stifel, Elizabeth; Headey, Derek D.; Hülsen, Vivien; Munasinghe, Dilusha; Ranucci, Immacolata; Sabai, Moe; van Asselt, Joanna; Weerasinghe, Krishani (International Food Policy Research Institute, 2025)
We assess water insecurity in Sri Lanka using the BRIGHT Integrated Household Survey data for 2024-2025. Key Findings • Compared to the 2016 DHS data, the 2024 BRIGHT results show moderate improvements in access to improved drinking water sources. Estate sector households show the greatest relative improvement, with the share using improved water sources increasing by approximately five percentage points. This shift is driven primarily by a 15-percentage-point rise in the use of protected wells, although nearly half (49%) of estate households continue to rely on rivers, springs, or tank water. • Most households in Sri Lanka report few insecurity experiences, and are therefore mostly water secure, with 90% not experiencing water insecurity. • Differences between groups are subtle and occur mainly between marginal and low levels of water security, rather than between fully secure and insecure households. • 68% of estate households (households on plantations), experienced at least water insecurity experience compared to only 28% of urban households and 33% of rural households. • Households in dry agroecological zones face slightly higher risks water insecurity (11%) com-pared to 9% of in both intermediate and wet zones. • Poverty is a key predictor of water insecurity. The poorest households are 6.8 times more likely to experience extreme water insecurity than the richest households. • Sri Lanka has lower levels of water insecurity than most other lower-middle income countries but needs to address poor water security in populations left behind. Improving water security in estate areas and in the dry zone should be national water security priorities